Comparison of Different Recovery Strategies After High-Intensity Functional Training: A Crossover Randomized Controlled Trial - Martínez-Gómez, Rafael; Valenzuela, Pedro L.; Lucia, Alejandro; Barranco-Gil, David (Frontiers in Physiology, 2022)
We aimed to determine whether ‘active’ or passive muscle contractions (surface neuromuscular electrical stimulation [NMES]) could enhance recovery after a high-intensity functional training (HIFT) session compared with total rest. The study followed a crossover design. Fifteen male recreational CrossFit athletes (29±8 years) performed a HIFT session (i.e., the Fran workout, a benchmark ‘workout of the day’ within CrossFit) and were randomized to recover for 15 min with either low-intensity leg pedaling (‘Exercise’), NMES to the lower limbs (‘NMES’), or total rest (‘Control’). Perceptual (rating of perceived exertion [RPE] and delayed-onset muscle soreness [DOMS] of the lower-limb muscles), physiological (heart rate, blood lactate and muscle oxygen saturation) and performance (jump ability) indicators of recovery were assessed at baseline and at different time points during recovery up to 24 h post exercise. No differences were found across conditions in the time needed to finish the HIFT session (p=0.410) or in the RPE reported immediately thereafter (p=0.106). However, a significant interaction (time by recovery strategy) effect was found for RPE (p=0.035) and DOMS (p=0.017). Post-hoc analyses revealed no significant differences across conditions, although there was a quasi-significant (p=0.061) trend towards a lower RPE with NMES compared with Control immediately after the 15 min-recovery. No significant interaction effect was found for the remainder of outcomes (all p>0.05). Except for a trend towards an improved perceived recovery with NMES compared with Control, low-intensity exercise, NMES and total rest seem to promote a comparable recovery of perceptual, physiological, and performance indicators after a HIFT session.